Study on Internet of Things electric system based on distributed smart terminals in demand side management - Zheng, G.L.; Zhang, L.; Chi, J.W. (Технічна електродинаміка, 2016)
Demand side management (DSM) plays an important role in enhancing electric power grid operation, which is sophisticated due to the versatility of different loads, the vast number of users as well as the distribution in space and time. Internet of things (IoT), goes without say, is a perfect solution to the bemused situation. In this paper, the construction and implementation scheme of an IoT electricity management system for DSM based on advanced electric smart control terminals and remote load controller (SRLC), is introduced. The system not only achieves real-time online monitoring but also achieves remote dynamic load management integrated with various functions, especially “load feature identification” and “dangerous load shedding” are applied successfully in student dormitories (5 buildings with 750 units) of Wuhan University. A transparent electricity management platform is created on both Wuhan University’s information WEB stations (called “cloud”) and all the relative students’ mobile phones (called “terminal”) by this IoT system. The equipment costs are discussed for installing this system. The application results show that the system provides an optimal decision and reliable reference data for building energy management, with additional advantages on safety, low cost and easy implementation with smart power grid or e-Energy. Управление спросом играет важную роль в улучшении работы электроэнергетических сетей, которые отличаются сложностью из-за наличия различных нагрузок, большого числа потребителей, распределения в пространстве и времени. Концепция «Интернет вещей» является идеальным решением для такого случая. В статье представлена схема построения и реализации этой концепции для систем управления спросом электроэнергии, основанной на современных управляющих смарт-терминалах и устройствах дистанционного регулирования нагрузок. Система обеспечивает мониторинг в режиме реального времени, дистанционное управление нагрузкой в соединении с различными функциями, и, в частности, функциями определения параметров нагрузки и аварийного сбрасывания нагрузки. Система успешно применяется в студенческих общежитиях (5 зданий с 750 блоками) Уханьского университета в Китае. Посредством системы «Интернет вещей» создана прозрачная платформа управления электроэнергией, которая включает информационные веб-станции Уханьского университета (называются «облаком») и мобильные телефоны всех студентов (называются "терминалами"). Применение системы показало, что она представляет собой оптимальное решение, дает надежную базу данных для управления энергопотреблением и обладает преимуществами: безопасностью, низкой стоимостью, простотой внедрения в смарт-энергосети или e-Energy. Управління попитом відіграє важливу роль у підвищенні роботи електроенергетичної мережі, яка є складною через багатогранність різноманітних навантажень, значної кількості користувачів та розподіл у просторі і часі. Зрозуміло, що система типу «інтернет речей» є ідеальним рішенням у даній ситуації. У статті представлено схему побудови та реалізації цієї концепції для управління попитом електроенергії на основі сучасних смарт-терміналів управління і пристроїв дистанційного регулювання навантаження. Система забезпечує онлайн моніторинг у режимі реального часу, дистанційне управління навантаженням, об'єднаного з різними функціями, і, зокрема, функціями визначення параметрів навантаження та аварійного скидання навантаження. Система успішно застосовується у студентських гуртожитках (5 будівель з 750 блоками) Уханьського університету у Китаї. За допомогою системи "інтернет речей" створена прозора платформа управління електроенергією, яка включає інформаційні веб-станції (називаються "хмари") Уханьського університету та мобільні телефони всіх студентів (називаються "термінали"). Застосування системи показало, що вона є оптимальним рішенням, дає надійну базу даних для управління енергоспоживанням та має такі переваги: безпека, низька вартість, легке впровадження у смарт-енергомережі та e-Energy.